2001
DOI: 10.1677/erc.0.0080047
|View full text |Cite
|
Sign up to set email alerts
|

Histological and biological evolution of human premalignant breast disease.

Abstract: Most human invasive breast cancers (IBCs) appear to develop over long periods of time from certain pre-existing benign lesions. Of the many types of benign lesions in the human breast, only a few appear to have significant premalignant potential. The best characterized of these include atypical hyperplasias and in situ carcinomas and both categories are probably well on along the evolutionary pathway to IBC. Very little is known about earlier premalignant alterations. All types of premalignant breast lesions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
243
1
16

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(275 citation statements)
references
References 86 publications
15
243
1
16
Order By: Relevance
“…38 It appears that greater genetic similarity lies between columnar cell change and tubular carcinoma than between columnar cell atypia and tubular carcinoma. 39,40 This brings forth a more robust and factcompatible hypothesis that would explain the majority of instances of columnar cell atypia without eliminating the possibility of progression, only rendering it a statistically much less likely event once an isolated columnar cell atypia lesion is formed.…”
Section: Discussionmentioning
confidence: 99%
“…38 It appears that greater genetic similarity lies between columnar cell change and tubular carcinoma than between columnar cell atypia and tubular carcinoma. 39,40 This brings forth a more robust and factcompatible hypothesis that would explain the majority of instances of columnar cell atypia without eliminating the possibility of progression, only rendering it a statistically much less likely event once an isolated columnar cell atypia lesion is formed.…”
Section: Discussionmentioning
confidence: 99%
“…41 In situ neoplastic lesions are considered to represent early stages in the multistep process of carcinogenesis. 42,43 A positive correlation has been suggested to exist between incidence of in situ breast cancers and overall breast cancer incidence in a particular population. 44 The prognosis among patients with histologically similar in situ lesions varies.…”
Section: Discussionmentioning
confidence: 99%
“…Although DCIS is pre-malignant (Pinder and Ellis, 2003), the modest improvement in breast cancer mortality attributable to such screening (Mandelblatt et al, 2009;Nelson et al, 2009) has suggested that many DCIS cases never progress to invasive disease, raising questions about the contribution of DCIS to the natural history of sporadic IDC (Allred et al, 2001;Burstein et al, 2004). In tumours containing both IDC and DCIS (IDC-DCIS), it is unclear whether the IDC component arises directly from DCIS; in tumours lacking DCIS, however, it is assumed that IDC arises de novo.…”
mentioning
confidence: 99%